DEVELOPMENT STRATEGIES IN ARSENAL AS A UPT DISSENLEKAL NAVY DISTRIBUTION LOGISTICAL SUPPLIES CLASS V - Ahmadi Ahmadi; Sutrisno Sutrisno; Arie Handito; I Nengah Putra A (JOURNAL ASRO, 2019)
Planning Information Systems and Information Technology (SI/IT) is part of the Strategic Plan (Renstra) of an institution. Every institution or organization must have a framework for developing information systems and documentation that is adequate and in line with developing systems and technologies. A comprehensive and integrated strategic information system planning is needed by a supply and logistics institution, especially Arsenal with capacity as the Dissenlekal Task Force of the Indonesian Navy Headquarters (Mabesal) in the management of TNI AL Class V logistics. In general this research is a efforts in developing strategic IS/IT planning and identification of their needs at the Arsenal institution as UPT Dissenlekal Mabesal to be more optimal so that it can be integrated and support the strategic planning of logistics supplies within the Navy. The basic concept in this research begins with the preparation of the IS/IT Strategic Plan framework using the Ward and Peppard model approach, then in the evaluation process the translation of the Strategic Plan IS/IT and management of the institution's basic tasks using Balance Scorecard. Some analytical methods such as Value Chain Analysis, SWOT Analysis, PEST Analysis and Five Force Model Analysis are used to analyze the internal and external institutional environment. Next is the McFarlan Analysis Strategic Grid method that is used for application portfolio planning. The results of this research are the recommendations of the relevant IS/IT blue print strategic planning owned by Arsenal UPT Dissenlekal Mabesal and development priorities by referring to the institution's main task plan based on data obtained through the implementation of analytical methods. The information produced will be integrated data for administrative needs and services for related work units. The optimal implementation of information data processing as well as increasing the role of stakeholders in the provision of infrastructure will improve the quality of logistics management services in the fifth grade of the Navy Navy logistics in a comprehensive and integrated manner. Keywords : IS/IT Strategic Planning, Ward and Peppard Model, information systems, information technology